Role of Vesicular Monoamine Transporter 2 Inhibitors in Tardive Dyskinesia Management - Sreeram, Venkatesh (Cureus, 2019)
Tardive dyskinesia (TD) is a distressing and disabling movement disorder that occurs with the use of chronic neuroleptic medications. TD is defined as involuntary athetoid or choreiform movements of head, trunk or limbs. Tongue, lower face, jaw, and extremities are commonly involved but pharyngeal, diaphragmatic, or truncal muscles are also sometimes involved affecting breathing, swallowing, speech, posture, gait, and mobility of an individual. TD is a debilitating movement disorder that requires timely intervention. Subtle tongue movements, tic-like facial movements or increased blink frequency could be some of the initial manifestations of TD. Our article is focused on the new advents in treating TD, their efficacy, and tolerability with emphasizing their side effect profile. The implication of a genetic marker vesicular monoamine transporter 2 (VMAT2), helped in investigating VMAT2 inhibitors for alleviating TD. Among the modalities tested, only VMAT2 inhibitors reported efficacy. However, the outcome of long-term use and its side effect profile can only be determined with longer studies utilizing large set data. More clinical trials are required to explore individual drug efficacy and their long-term adverse effects. We aim to provide an overview of TD management, illustrating the priority of VMAT2 inhibitors and to determine the importance of selecting an optimal medication. A search through PubMed with terms "Tardive dyskinesia" and "VMAT2 inhibitors" was carried out. Several treatment modalities were tested to control the symptoms of TD with limited benefit. However, VMAT2 inhibitors showed improvement in the Abnormal Involuntary Movement Scale (AIMS) rating scale for TD. Valbenazine and deutetrabenazine (d-TBZ) were recently approved by the Food and Drug Administration (FDA) for treating TD in adults.